1991
DOI: 10.1111/j.1432-1033.1991.tb16461.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of soluble aminopeptidases from Saccharomyces cerevisiae

Abstract: Plasmids capable of complementing lupl, lap2 and lap3 mutations [R. J. Trumbly and G. Bradley (1983) J. Bucteriol. 156, [36][37][38][39][40][41][42][43][44][45][46][47][48] were isolated from a yeast YEpl3 library by screening for activity against the chromogenic aminopeptidase substrate L-leucine P-naphthylamide in intact yeast colonies. The genomic inserts were shown to contain the structural genes for aminopeptidases yscII, yscIII and ysclV. Plasinids containing the gene encoding aminopeptidase yscII of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…In addition, the enzymatic reaction was inhibited in the presence of an excess of Zn 2ϩ , which suggests that this peptidase belongs to the M1 family of zinc-binding metalloproteases. Aminopeptidase II from S. cerevisiae is believed to be involved in the cellular supply of leucine from externally offered leucine-containing di-or tripeptide substrates (30). We found similar properties of S. boulardii peptidase against the peptide L-Leu-Gly-Gly.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In addition, the enzymatic reaction was inhibited in the presence of an excess of Zn 2ϩ , which suggests that this peptidase belongs to the M1 family of zinc-binding metalloproteases. Aminopeptidase II from S. cerevisiae is believed to be involved in the cellular supply of leucine from externally offered leucine-containing di-or tripeptide substrates (30). We found similar properties of S. boulardii peptidase against the peptide L-Leu-Gly-Gly.…”
Section: Discussionsupporting
confidence: 64%
“…Zinc-binding metalloproteases can be grouped together as a superfamily known as the metzincins on the basis of their sequence similarity (27). Family M1 includes bacterial aminopeptidase N (EC 3.4.11.2), mammalian aminopeptidase N (EC 3.4.11.2), mammalian glutamyl aminopeptidase (EC 3.4.11.7) or aminopeptidase A, leukotriene A-4 hydrolase (EC 3.3.2.6) (28), alanine/arginine aminopeptidase from S. cerevisiae (gene AAP1) (29), and aminopeptidase II (gene APE2) from S. cerevisiae (30). The similarities between the sequences of human, rat, and yeast aminopeptidases that contain the (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…F-pNA was used as a substrate for the determination of the pH optimum, the pH stability, and the temperature stability of the purified enzyme. The optimal pH is 5, which is different from the pH optima reported for A. niger ApsA and other intracellular aminopeptidases, such as the yeast aminopeptidases which all have pH optima around 7.5 (1,4,7,11).…”
Section: Resultsmentioning
confidence: 62%
“…vp165 as an Aminopeptidase-Comparison of the predicted amino acid sequence of vp165 with those in the sequence data banks revealed that the large 785-amino acid C-terminal portion of vp165 contained regions with high homology to domains conserved between the mammalian aminopeptidases A and N (23, 24), aminopeptidase yscII from Saccharomyces cerevisiae (25), and aminopeptidase N from Lactococcus lactis (26), as well as the recently described thyrotropin-releasing hormone degrading enzyme from rat (27). The similarity is highest in a stretch of 349 amino acids, where the overall identity to vp165 ranges between 36% for thyrotropin releasing hormone degrading enzyme and 45% for aminopeptidase yscII (Fig.…”
Section: Resultsmentioning
confidence: 99%